Time trend and Age-Period-Cohort analysis of potentially HPV-related oral and pharyngeal cancer incidence in Singapore between 1968 and 2017. (January 2023) - Peres, Marco A.; Huihua, Li; Antunes, Jose Leopoldo F.; Perea, Lillia Magali Estrada; Iyer, Narayanan Gopalakrishna; Peres, Karen G.
Highlights: The incidence of HPV-related oral and pharyngeal cancer seems stable between 1968 and 2017 which is not the case in much of the world. The incidence of HPV-unrelated oral and pharyngeal cancers declined between 1968 and 2017 which is the case in much of the Western world. Young cohorts had the lowest incidence of HPV-related cancers. HPV-related cancers increased from 1988 to 1997. Abstract: Objectives: To examine trends and age-period-cohort effects (APC) on oral and pharyngeal cancers incidence in Singapore between 1968 and 2017 by human papillomavirus (HPV) status. Methods: All diagnosed oral and pharyngeal cancers and population size were extracted from the Singapore Cancer Registry and the Department of Statistics Singapore, respectively. Anatomical subsites were used as a proxy for HPV infection . Prais-Winsten regression assessed trends of age-standardised incidence rate (ASIR) (per 100, 000 person-years); Poisson regression assessed APC effects on HPV-related and HPV-unrelated cancers. Results: Over 50 years, 1, 618 HPV-related and 2, 977 HPV-unrelated oral and pharyngeal cancers were diagnosed, with the highest ASIR in Indians (6.93), followed by Chinese (2.81), and Malays (1.81). Overall, ASIR HPV-related cancers were stable while HPV-unrelated cancers decreased. The male–female ASIR ratio reduced from 5.82 (1968–1977) to 4.0 (2008–2017) for HPV-related cancers, and from 2.58 (1968–1977) to 1.52 (2008–2017) for HPV-unrelated cancers. HPV-unrelated ASIR in males decreased, but in females only among Indians. HPV-related ASIR decreased only among Indian females. The cohort born between 1983 and 1992 had the lowest incidence of HPV-related cancers in males but the highest in HPV-unrelated cancers. Period effect mainly contributed to HPV-related cancer among males with increased incidence after 1997. Overall, the age effect was more pronounced in males. Conclusions: HPV-related cancers accounted for 1/3 of oral and pharyngeal cancers. A significant decline was observed only for HPV-unrelated cancers. The cohort effect was mainly attributed to HPV-unrelated cancer incidence, while the period effect largely contributed to HPV-related cancer incidence, but only among males.